The COVID-19 Pandemic Impact on the Outcome of Medically Assisted Reproduction Pregnancies - Huri, Mor; Noferi, Virginia; Renda, Irene; Piazzini, Francesca; Benemei, Silvia; Coccia, Maria Elisabetta (Frontiers in Reproductive Health, 2022)
Background: The impact of COVID-19 pandemic on pregnancy is not well understood. During the outbreak, the initial approach suggested by the major Societies was to postpone all non-urgent assisted reproductive technology (ART) treatments. Nevertheless, the Italian Society of Fertility and Sterility and Reproductive Medicine considered ethically correct to proceed with ART treatments, as infertility rate is increasing over time, with a consistent decline in live birth rate. The objective of our study was to assess the impact of COVID-19 pandemic on ART pregnancies outcome, in terms of early pregnancy loss, overall success rate and live birth rate. Methods: We conducted a single-Center retro-prospective cohort study. Patients undergoing ART treatments from March 1st, 2020, to February 28th, 2021 (pandemic ART cohort, pART; n=749) and from March 1st, 2019, to February 29th, 2020 (control cohort, CTR; n=844) were enrolled. The study had a duration of 24 months. Patients underwent baseline SARS-Cov-2 nasopharyngeal swab; quantitative serum beta human chorionic gonadotropin to assess pregnancy; pelvic transvaginal ultrasound; follow-up until delivery. The study took place at the ART Center of the University Hospital in Florence, Italy. Results: There were not statistically significant differences on implantation rate (pART 0.348±0.034 vs CTR 0.365±0.033, CI= 95%, p 0.49), clinical pregnancy rate (pART 0.847±0.044 vs CTR 0.864±0.038, CI= 95%, p 0.56) and ectopic pregnancy rate (pART 0.008±0.011 vs CTR 0.01±0.011, CI= 95%, p 0.79). First trimester miscarriage rate was not different between the groups (pART 0.224±0.056 vs CTR 0.213±0.05, CI= 95%, p 0.77), nor second trimester miscarriage rate (pART 0.018±0.018 vs CTR 0.019±0.017, CI= 95%, p 0.95). Live birth rate remained unchanged during the pandemic (pART 0.22±0.03 vs CTR 0.239±0.029, CI= 95%, p 0.37), and stable even compared to our Center rate between 2015-1019 (pART 0.222±0.03 vs general rate 0.224±0.014, CI= 95%, p 0.83). Conclusion: The COVID-19 pandemic did not cause a statistically significant change in the live birth rate and in pregnancy loss rate. ART during COVID-19 pandemic can be considered fair and safe, ethically and medically appropriate. Patients and physicians should be reassured that ART pregnancy outcomes do not seem to be jeopardized by the pandemic state.